Economic speeds defined by the cost index - Rolando Antonio Corradini Neto (2013)
The competitive market will keep asking airlines for better services and lower prices, imposing pressure on costs. Therefore, it is important for an airline to establish operational standards that will allow an aircraft to be operated more efficiently. The implementation of the Economic Speeds defined by the Cost Index can represent significant operating cost reductions when compared to simply flying Fixed Speeds. Different aircraft models today are equipped with Flight Management Computers (FMC) that are capable of automatically calculating the Economic Speeds based on the Airline Cost Index. In the other hand, several aircraft types manufactured by world leading companies and flown by many airlines around the globe are equipped with FMCs that do not have this capability. Accordingly, this work focuses on the Economic Speeds defined by the Cost Index. More specifically, the Cost Index Methodology is discussed and its fundamentals are applied to the climb phase of the flight. Finally, a methodology for the generation of a practical guidance that allows the determination of the Economic Climb Speed Schedule during the daily operation is presented, allowing an airline with a fleet equipped with FMCs not capable of automatically calculating the Economic Climb Speed Schedule to take advantage of the potential operating cost reduction. The proposed methodology can be applied on the development of a calculation software to be installed on an Electronic Flight Bag (EFB) or to be used for generating data to be sent directly to the flight crew in the cockpit through a Datalink System. In case an EFB or a Datalink System are not an alternative, the proposed methodology leads to the Economic Climb Speed Schedule Table, a practical guidance that allows the flight crew to determine the Economic Climb Speed Schedule for an Airline Cost Index and different conditions of aircraft weight, cruise altitude and speed, with corrections for temperature and wind variations. Since corrections for temperature and wind variations can be understood as a simplification that permits the Economic Climb Speed Schedules to be presented through a table, it is necessary to investigate the impact of this simplification on the optimization. Therefore, the operating costs for an aircraft flying the Economic Climb Speed Schedule calculated for each specific condition is compared with that same aircraft flying the speeds obtained from the suggested Table. Finally, a Study Case analyses the impact on the operating costs for an aircraft flying the speeds obtained from the Economic Climb Speed Schedule Table in comparison with flying a Fixed Climb Speed Schedule.